Spontaneous Pneumothorax: A Rare Complication of Neurofibromatosis Type 1 Associated Diffuse Lung Disease - Emma I. Sherfinski; Mark H. Cooper (Marshall Journal of Medicine, 2022)
The visually striking neurocutaneous findings of neurofibromatosis type 1 (NF1) are well recognized and have been well documented throughout scientific literature. While not uncommon, the pulmonary manifestations of NF1 are unknown to many physicians. Complications of NF1 associated diffuse lung disease (NF-DLD) include pulmonary hypertension, pulmonary artery stenosis, subpleural cysts, and spontaneous pneumothorax. We present a case of a 34-year-old male with NF-DLD found incidentally in adolescence with previous apical bleb repair, presenting nearly twenty years later with spontaneous pneumothorax. In NF1 patients with pulmonary complaints, NF-DLD should be assessed with computed tomography (CT) and physicians should be familiar with associated complications.